Homeobox genes are expressed in the retina and brain of adult goldfish. - Levine, E M (1993)
The goldfish (Carassius auratus) visual pathway displays continuous growth and plasticity throughout life. Since homeobox genes are important transcriptional regulators in development, we searched for homeobox genes in the adult goldfish retina and brain. Using the PCR, we discovered a repertoire of homeobox sequences expressed in these tissues. In addition to isolating homeodomain sequences found in the vertebrate Hox gene clusters, a sequence identical to the chicken CHox7 homeodomain was characterized. Furthermore, a sequence with significant homologies to the Xenopus XIHbox8 and leech Htr-A2 homeodomains was identified, and these sequences may define an additional class of homeodomain. Finally, a sequence belonging to the paired class (prd) of homeodomains is reported. Homeobox gene expression in the adult goldfish retina and brain may be associated with the persistent developmental features of these tissues.